A Composite End Point of Graft Status and eGFR at 1 Year to Improve the Scientific Registry of Transplant Recipients' Five-Tier Rating System. Issue 8 (August 2022) - Wang, Kaicheng; Deng, Yanhong; Stewart, Darren; Formica, Richard N.
Significance Statement: Quantifying meaningful differences in competency of kidney transplant programs based on 1-year survival rates is challenging because of relatively few allograft failure events per program and increasing homogeneity in program performance. In this study, the researchers found that compared with the traditional end point of graft status (allograft failure at 1-year post-transplant), a composite end point that incorporates a measure of allograft function—the recipients' eGFR <30 ml/min per 1.73 m 2 or graft failure at 1 year—performed better in differentiating between transplant programs with respect to long-term deceased donor graft outcomes. Incorporating granular measures of allograft function into performance metrics instead of solely using a binary (functioning/failed) indicator has the potential to improve patient care by prioritizing allograft function as a measure of program quality. Visual Abstract: Abstract : Background: Performance of kidney transplant programs in the United States is monitored and publicly reported by the Scientific Registry of Transplant Recipients (SRTR). With relatively few allograft failure events per program and increasing homogeneity in program performance, quantifying meaningful differences in program competency based only on 1-year survival rates is challenging. Methods: We explored whether the traditional end point of allograft failure at 1 year can be improved by incorporating a measure of allograft function ( i.e., eGFR) into a composite end point. We divided SRTR data from 2008 through 2018 into a training and validation set and recreated SRTR tiers, using the traditional and composite end points. The conditional 5-year deceased donor allograft survival and 5-year eGFR were then assessed using each approach. Results: Compared with the traditional end point, the composite end point of graft failure or eGFR <30 ml/min per 1.73 m 2 at 1-year post-transplant performed better in stratifying transplant programs based on long-term deceased donor graft survival. For tiers 1 through 5 respectively, the 5-year conditional graft survival was 72.9%, 74.8%, 75.4%, 77.0%, and 79.7% using the traditional end point and 71.1%, 74.4%, 76.9%, 77.0%, and 78.4% with the composite end point. Additionally, with the five-tier system derived from the composite end point, programs in tier 3, tier 4, and tier 5 had significantly higher mean eGFRs at 5 years compared with programs in tier 1. There were no significant eGFR differences among tiers derived from the traditional end point alone. Conclusions: This proof-of-concept study suggests that a composite end point incorporating allograft function may improve the post-transplant component of the five-tier system by better differentiating between transplant programs with respect to long-term graft outcomes.